Francisco Antonio Lacaz Netto (1911-1991): um estudo biográfico - Calabria, Angelica Raiz [UNESP] (2015)
Francisco Antonio Lacaz Netto was born on 06th February, 1911, in Guaratinguetá, São Paulo state. He graduated in Pharmacy, Geographic Engineering and Mathematics. As professor, he worked only in Mathematics area. He worked at several schools and institutions, one of them the Instituto Tecnológico de Aeronáutica (ITA), located in São José dos Campos, São Paulo, where he was hired as associate university lecturer since its inception in 1950. Besides being university lecturer, Lacaz has invited professionals to make part of the first staff of the Mathematics Department of ITA, they later became important Brazilian researchers. He was head of the Mathematics Department and then dean at ITA. A close friend among the students, he was honoured several times, such as the accolade Lacaz Netto. Professor Lacaz has a considerable bibliography consisting in some mathematical papers and several textbooks. He retired in the ITA in 1981 as professor. Thereby, this research aims to add information to the History of Mathematics in Brazil and It presents a biographical study about Francisco Antonio Lacaz Netto, describing his professional training, university lecturer career, major works and honours, highlighting his career at ITA and also his dedication as professor which present him as Math Educator